Ductile Materials Stress Upturn at High Strain Rates - Partom, Y (European Journal of Applied Sciences, 2023)
Ductile materials (mainly metals) exhibit a sharp stress upturn, which is not specific to a certain type of material, at strain rates around 103 to 104/s. It is important to consider such stress high-rate upturn when dealing with shock loading and unloading. Using classical strength models, usually calibrated at not so high rates, may lead to errors when considering high-rate loading under not so high pressures. Here we model high-rate upturn on the macroscale. We assume that the upturn mechanism is also the mechanism responsible for the 4th power law mechanism, put forward by Swegle and Grady. In the past we calibrated our overstress dynamic viscoplasticity model for aluminium from 4th power law data. Here we use this calibration to predict the high-rate stress upturn response.